PENGARUH DUKUNGAN REKAN KERJA DAN DUKUNGAN KELUARGA TERHADAP KINERJA DENGAN JOB EMBEDDEDNESS SEBAGAI PEMEDIASI PADA ANGGOTA KEPOLISIAN SATLANTAS POLRESTA BANDA ACEH - Noratul Mukarramah; Nur chalil (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to determine the effect of coworker and family support on performance with job embeddedness as a mediator. Empirical study was conducted on police personnel in Satlantas Polresta of Banda Aceh using questionnaires as research instruments, in which the sample in this study is 86 respondents. Nonprobability Sampling is used as sampling technique with Sensus Sampling method. The Hierarchical Linear Modeling (HLM) method was used as a data analysis method using the IBM SPSS 20 software. The results of this study indicate that the coworker and family support have a positive and significant effect on performance, job embeddedness have a positif and significant effect on performance, and the coworker and family support have a positif and significant effect on job embeddedness. In addition to the results obtained that job embeddedness mediate the positive influence of coworker and family support on performance.